Acute Effect of Electroacupuncture on Hippocampal Long-term Potentiation of Rats in Vivo - Qianqian SUN; Yishu CHEN; Xinyi GUO; Xiaokuo HE (康复学报)
Objective:To investigate the effects of single electroacupuncture (EA) at Shenting and Baihui on hippocampal population spike (PS) response and long-term potentiation (LTP) of perforant path-dentate gyrus (PP-DG) granule cells synapse in anesthetized normal rat and explore the underlying mechanisms.Methods:A total of 20 male Wistar rats were randomly divided into the EA group (n=10) and the control group (n=10). Rats were anesthetized with Urethane, and placed in a stereotaxic apparatus. The PS amplitude in response to perforant path stimulation was record. The paired pulse stimulation was given at two inter-pulse intervals, then theta burst stimulation was applied to perforant path before and after EA. Acupuncture needles were gently inserted into Shenting and Baihui of rats after acquiring steady response in dentate gyrus. Stimulation was applied to these acupoints with 2 mV of continuous wave (2 Hz) for 30 minutes using an EA apparatus.Results:Compared with the control group, the hippocampal PS amplitude and LTP were significant increased in EA group (P<0.05).Conclusion:EA at Shenting and Baihui could raise up the PS amplitude in response to perforant path stimulation, and enhance LTP, which may related to the modulating functions of interneuron in hippocampus.